A time‐ and cost‐saving method to check the point‐to‐point distribution of soil improvers. Issue 2 (22nd January 2021) - Malferrari, Daniele; Laurora, Angela; Brigatti, Maria Franca; Di Giuseppe, Dario; Faccini, Barbara; Coltorti, Massimo
Abstract: Background : In recent times, also in compliance with several sustainable agriculture rules, the use of soil conditioners, such as zeolites, progressively increased. Zeolites are minerals characterized by unique physical‐chemical properties, which make them able to control the mobility of water, ammonium and other cations in soils. As zeolites do not exhaust their properties over time, it would be appropriate to check for their correct distribution in the amended soil. Aims : We present an efficient and inexpensive method to measure the point‐to‐point amount of zeolite spread in the soil through the analysis of a single ( i.e ., one peak) X‐ray powder diffraction signal. Methods : The procedure requires the preparation of a calibration curve using known quantities of non‐amended soil, zeolite and of an internal reference standard. The amount of zeolite is calculated by comparing the intensities of the selected signal in unknown sample with its analogue in the calibration curve. Results : The method returned a small underestimation (about 12 weight %) of the measured values compared to those expected which depend nearly exclusively on the valuation of the apparent density of the soil, whereas it is not affected by the type and number of phases present in the soil and in the amendant. Conclusions : The proposed method allows to check for the regular distribution of zeolite in soil, but we are confident that it could also be conveniently generalized to all the applications that require the quantitative determination of mono or polyphasic crystalline materials within a complex mixture like soil.